Fisheries: monitoring fish stocks in Lake Victoria - Mkumbo, Oliva (Technical Centre for Agricultural and Rural Cooperation, 2005)
Oliva Mkumbo reports on how hydroacoustic surveying is contributing to the sustainable management of Lake Victoria's fisheries.